2009
DOI: 10.3844/jssp.2009.104.111
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Psychological Factors-Does it Impact the Choice of Advertising Medium?

Abstract: Problem statement:Advertising is a multidimensional phenomenon that has been studied in several disciplines. It is one of the most fascinating phenomena in modern capitalist markets. It is pervasive, perplexing, multidimensional and unfathomably rich. The effectiveness of advertising depends on both the quality of the product being advertised and the quality of the ad itself and also the media context in which the ad appears. Personal factors (such as gender and age) and psychological factors (for example stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Accordingly, success of an advertising campaign heavily depends on the precise selection and identification of the target audience, selection of ideal medium to advertise, right content creation of the advert with a clear message, the creative strategy used to carry out the campaign and the assessment of the advertising results respectively (Ghayoomi Javinani & Shokri, 2014). Idris, Shukri, and Khatibi (2009) discusses that the effectivity of an advertisement depends on both the quality of the advertisement along with the quality of the product that is promoted aided by the context in media which the advertisement occurs. Attracting Consumer Attention is the main goal behind the marketing of a certain product.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, success of an advertising campaign heavily depends on the precise selection and identification of the target audience, selection of ideal medium to advertise, right content creation of the advert with a clear message, the creative strategy used to carry out the campaign and the assessment of the advertising results respectively (Ghayoomi Javinani & Shokri, 2014). Idris, Shukri, and Khatibi (2009) discusses that the effectivity of an advertisement depends on both the quality of the advertisement along with the quality of the product that is promoted aided by the context in media which the advertisement occurs. Attracting Consumer Attention is the main goal behind the marketing of a certain product.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investigating how a campus recreation department markets their programs allows campus recreation professionals to study marketing strategies, and hence promote their product appropriately. Advertising for campus recreation can be a valuable tool to attract participants' attention and to inform them about new and existing programs (Idris, Yajid, & Khatibi, 2009). As the campus recreation profession recognizes the significance of appropriately marketing their programs they will be expected to play key roles in the transformation of the campus environment.…”
Section: Marketing Strategy For Campus Recreationmentioning
confidence: 99%
“…Finding a successful advertising medium for potential consumers can be quite an undertaking. Consumers have their own favorite advertising medium that affects their behavior and increases the likelihood that they will find the product pleasing and appealing (Idris, Yajid, & Khatibi, 2009). Each day consumers are bombarded with a variety of messages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, advertising forms the motivational-need sphere of a person and in his mind influences the formation of certain values and ideas related to the consumption of products or services. There are various models of the influence of advertising on consumers, including young people: R. Batra, M. L Ray [1], Izian Idris, Mohd Shukri Ab Yajid and Ali Khatibi [2], W. J. McGuire [1], W. Wells, J. Burnett, S. Moriarty [4]), which showed that in the process of perception of advertising, the impact on the motivational and value-semantic spheres of personality is carried out through the translation of actual meanings of different nature, aimed at preserving and rooting of stereotypes of advertising messages in the consciousness. This problem is of particular relevance in relation to the student audience, because at this age value and semantic attitudes of personality, patterns and models of social behavior are formed.…”
Section: Introductionmentioning
confidence: 99%